KESEPIAN PADA NARAPIDANA DI LEMBAGA PEMASYARAKATAN KEDUNGPANE SEMARANG DITINJAU DARI DUKUNGAN SOSIAL KELUARGA DAN STATUS PERKAWINAN - Luh Putu Shanti K, Anisah Lailatun Nur (Jurnal Psikologi, 2011)
The purposes of this research were to examine the correlation between social support from family and loneliness on the prisoner at Kedungpane Prison Semarang, also to examine the difference of loneliness between married prisoner and unmarried prisoner. Data analysis for the first hypothesis resulted in rxy = -0,432; p = 0,001 (p < 0, 01), indicated that there was very significant negative correlation between social support from family and loneliness. Effective contribution from family social support to loneliness equal to 18, 7%, whereas 81, 3% influenced by other variables. Data analysis for the second hypothesis resulted in t = 8,038; p = 0,000 (p < 0, 01), showed that there were very significant difference of loneliness between married prisoner and unmarried prisoner. The average (mean) score of loneliness on married prisoner was 58, 13 while the mean score on unmarried prisoner was 75, 33, showed that loneliness on unmarried prisoner was higher than one on married prisoner.